Inside Front Cover: Topology and Interactions in the Photonic Creutz and Creutz‐Hubbard Ladders (Adv. Quantum Technol. 2/2020). Issue 2 (13th February 2020) - Zurita, Juan; Creffield, Charles E.; Platero, Gloria
Abstract : The equations that guide the propagation of light in certain circumstances can be mapped to those of quantum mechanics. This allows the simulation of quantum systems in photonic setups such as waveguide lattices, featured in the cover image. In article number 1900105, Juan Zurita, Charles Creffield and Gloria Platero analyze the possible use of a photonic lattice to simulate a strongly‐correlated topological insulator with AharonovBohm localization dynamics. The intense repulsive interaction considered can actually bind particles together, and the doublon formed in this way can feature similar dynamics to the single‐particle case, but for different values of the parameters of the system.